Conclusion: Rethinking Business–Society Relations in Botswana - Langtone Maunganidze; France Maphosa (Palgrave Macmillan, Cham, 2022)
There is a clear dissonance between what companies in Botswana publicly portray as corporate social responsibility (CSR) or corporate citizenship (CC) behaviour and the reality on the ground. Evidence presented in this book shows that the logics and forms of business–society interactions are complex and the effects on stakeholders are multifarious. This chapter synthesizes the overarching characteristics and dimensions of CSR initiatives and also assesses the extent to which the activities are substantive or symbolic. The conclusion is that while the different business sectors in Botswana have recently embraced the philosophy of giving back to communities, the impact on their activities has been limited. What is glaringly missing is a strategic engagement of communities that transforms them from being dependent to participatory stakeholders. Most firms are actually investing more in projecting themselves as good corporate citizens than in addressing genuine community needs.